Identification of the EcoKI and EcoR124I Type I restriction--modification enzyme subunits by non-equilibrium pH gradient two-dimensional gel electrophoresis - Nguyen, L D; Cajthamlová, K; Nguyen, H T; Weiser, J; Holubová, I; Weiserová, M (Folia microbiologica, 2002)
Effectively optimized and reproducible procedure for monitoring the composition of type I restriction-modification endonucleases EcoKI and EcoR124I by non-equilibrium pH gradient two-dimensional (2-D) gel electrophoresis is described. Three subunits of the enzyme complex, which widely differ from one another in their isoelectric points and molar mass, were identified in crude cell extracts of E. coli. For the first time all three subunits of both EcoKI and EcoR124I were detected as distinct spots on a single 2-D gel. A sensitive immunoblotting procedure was suggested suitable for routine use in determining the identity of individual subunits. Potential application of this method for detailed studies of regulation of the function and stoichiometry of the enzyme complexes is discussed.
Keywords: Electrophoresis, Gel, Two-Dimensional; molekulová hmotnost; DNA Restriction Enzymes; místně specifická DNA-methyltransferasa (adenin-specifická); Isoelectric Point; DNA restrikčně-modifikační enzymy; Blotting, Western; 2D gelová elektroforéza; izoelektrický bod; Escherichia coli; DNA Restriction-Modification Enzymes; western blotting; restrikční endonukleasy typu I; Deoxyribonucleases, Type I Site-Specific; Site-Specific DNA-Methyltransferase (Adenine-Specific); restrikční enzymy; Molecular Weight